Model predictive direct power control of three-level T-type inverter-fed doubly-fed induction generator for wind energy system - Ngo, Van Quang Binh; Nguyen, Khanh Quang; Nguyen, Tu Ha; Hoang, Dinh Long; Dao, Quoc Chinh (Hue University Journal of Science: Natural Science, 2021)
The paper proposes a simplified direct power control strategy of a doubly-fed induction generator fed by a three-level T-type inverter based on finite control set model predictive control. A mathematical model based on grid voltage orientation was employed to determine the predictive values of the stator flux, rotor current, and capacitor voltages for all feasible rotor-side inverter output voltages. The active and reactive powers were calculated by using the grid voltage and the rotor current. A cost function was applied to track the active and reactive powers, maintain the balance of capacitor voltages, and reduce the common-mode voltage. The best switching control input was chosen by minimizing the cost function and implemented to the inverter. Different operating conditions of wind turbine systems were studied with Matlab/Simulink environment. The simulation results validate the improved performance of the proposed method compared with the classical control in terms of transient response and steady-state conditions.